Development process with schedulability analysis (DePSA) integrated approach for real time systems [electronic resource] - Yavuz Selim Sengoz, 1980- (2011)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2011